NILAI PENDIDIKAN KARAKTER DAN KEARIFAN LOKAL DALAM CERITA RAKYAT SUMBAWA - Desmawanti, Rosa (Universitas Islam Negeri Mataram, 2022)
This study deals with the values of character education and local wisdom in Sumbawa Regency’s folklores.. This study aims to describing the types, content, the values of character education, the local wisdoms, and relevance with literature taught in elementary school. There are three sub-districts in Sumabawa Regency, they are Plampang, Lenanggular, and Utan. The subjects of this study were folklores entitled Paruma Ero, Batu Tongkok, Bola Sabale, and Meke Serep. The sampling technique was purposive sampling. The technique of the data analysis employs flow model analysis starting from collection, reduction, service, and conclusion. The raw data from the fields were selected, grouped, and arranged into an easy-to-analyze form to conclude. The research result from folklores ere; a myth, a legend, and a tale. The four folklores contain many character education values to impart curiosity, caring about environment, peace, high-determination, spirit of nationality, responsibility, honesty, creativity, religion, discipline, and independence.